THE RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND STUNTING INCIDENCE IN NAGARI MUARO SIJUNJUNG DISTRICT WEST SUMATERA PROVINCE IN 2024 - Adethia, Kismiasih; Arte Tifa, Rezeki Syofiani; Utami, Lisa Putri; Pinem, Srilina; Pitalola, Diah (Journal of Public Health Science, 2025)
Background: The incidence of stunting in West Sumatra Province has increased significantly in 2021, with a prevalence of 23.3% to 25.2% in 2022. This figure can be considered a setback because it is above the national figure (21.6%), where Sijunjung Regency is the fourth largest contributor to stunting rates, amounting to 30% based on the results of the Indonesian Status Survey (SSGI) by the Research and Development Agency of the Ministry of Health of the Republic of Indonesia in 2022 (Ministry of Health of the Republic of Indonesia, 2022). The high rate of stunting is triggered by various factors. According to the World Health Organization (WHO, 2014), factors that cause stunting experienced by children include nutritional status, exclusive breastfeeding, lack of nutritious food consumption, and disease infections. In addition, there are other causes that influence the nutritional status of stunting, namely maternal characteristics (age, education level, occupation, and height of the mother). Methods: This quantitative research used a case-control design. The sample size was 50 children aged 1-3 years in Muaro Sijinjung Village, Sijunjung Regency, in May-June 2024. The sampling technique used was purposive sampling. The research instrument used a questionnaire, and bivariate analysis used the Chi-Square Test. Data processing was done through editing, coding, entry, and tabulation. This study adhered to the ethical principles of research, including informed consent from respondents and confidentiality of their personal data. Results: There is a relationship between maternal height and maternal nutrition with the incidence of stunting with a P value of 0.00 and there is no relationship between maternal age and the incidence of stunting with a P value-e of 0.233. Conclusion: There is a significant relationship between maternal height and maternal nutrition with the incidence of stunting and there is no significant relationship between maternal age and the incidence of stunting in Muaro Sijinjung Village, Sijunjung Regency in 2024. It is hoped that this research can increase knowledge and insight to prevent stunting in children